Modelling and stabilization of a wireless network control system with time delay. (January 2018) - Ma, Junqing; Pan, Feng; Zhou, Liuwei; Zhou, Wuneng; Wang, Zehao
This paper investigates the problem of modelling and stabilization for a wireless based network control system with time delay. A model for the discrete-time system with time-varying delay is established to describe the system, and a static controller is designed that takes the feedback from both state and output into account. Based on Lyapunov stability theory and the linear matrix inequalities method, a new criterion is presented for stabilizing the discrete-time system with time-varying delay, and the corresponding controller parameter is obtained. A numerical example is given to demonstrate the effectiveness of the proposed approach.